Exposure to endocrine disruptors 17alpha-ethinylestradiol and estradiol influences cytochrome P450 1A1-mediated genotoxicity of benzo[a]pyrene and expression of this enzyme in rats. (1st May 2018) - Stiborová, Marie; Dračínská, Helena; Bořek-Dohalská, Lucie; Klusoňová, Zuzana; Holecová, Jana; Martínková, Markéta; Schmeiser, Heinz H.; Arlt, Volker M.
Graphical abstract: Effects of 17α-ethinylestradiol (EE2) and estradiol (ESTRA) on DNA adducts formed by benzo[ a ]pyrene (BaP). Highlights: 17α-ethinylestradiol( EE2) and estradiol affect genotoxicity of benzo[ a ]pyrene (BaP) in rats. Cytochrome P450 (CYP) 1A1 and 1B1 are induced in rats by BaP but not EE2 and estradiol. Exposure of rats to EE2, estradiol and BaP decreased BaP-DNA adduct formation in vivo . The decrease results from inhibition of CYP1A1-mediated BaP activation by EE2 and estradiol. Abstract: Endocrine disruptors (EDs) are compounds that interfere with the balance of the endocrine system by mimicking or antagonising the effects of endogenous hormones, by altering the synthesis and metabolism of natural hormones, or by modifying hormone receptor levels. The synthetic estrogen 17α-ethinylestradiol (EE2) and the environmental carcinogen benzo[ a ]pyrene (BaP) are exogenous EDs whereas the estrogenic hormone 17β-estradiol is a natural endogenous ED. Although the biological effects of these individual EDs have partially been studied previously, their toxicity when acting in combination has not yet been investigated. Here we treated Wistar rats with BaP, EE2 and estradiol alone or in combination and studied the influence of EE2 and estradiol on: ( i ) the expression of cytochrome P450 (CYP) 1A1 and 1B1 in rat liver on the transcriptional and translational levels; ( ii ) the inducibility of these CYP enzymes by BaP in this rat organ; ( iii ) the formation of BaP-DNA adducts in rat liver in vivo ; and ( iv ) the generation of BaP-induced DNA adducts after activation of BaP with hepatic microsomes of rats exposed to BaP, EE2 and estradiol and with recombinant rat CYP1A1 in vitro . BaP acted as a strong and moderate inducer of CYP1A1 and 1B1 in rat liver, respectively, whereas EE2 or estradiol alone had no effect on the expression of these enzymes. However, when EE2 was administered to rats together with BaP, it significantly decreased the potency of BaP to induce CYP1A1 and 1B1 gene expression. For EE2, but not estradiol, this also correlated with a reduction of BaP-induced CYP1A1 enzyme activity in rat hepatic microsomes. Further, while EE2 and estradiol did not form covalent adducts with DNA, they affected BaP-derived DNA adduct formations in vivo and in vitro . The observed decrease in BaP-DNA adduct levels in rat liver in vivo resulted from the inhibition of CYP1A1-mediated BaP bioactivation by EE2 and estradiol. Our results indicate that BaP genotoxicity mediated through its activation by CYP1A1 in rats in vivo is modulated by estradiol and its synthetic derivative EE2.